Stories for circle time and assembly : developing literacy skills and classroom values - Leicester, Mal (Routledge, 2006)
Circle time is a very popular activity in today's schools and creates a safe, fun environment where children can think about their relationships, their behaviour, and be honest about their problems and feelings. In this book, the highly successful and popular author Mal Leicester offers a range of lively and engrossing stories, poems and songs for use in circle time activities and assemblies. They are specially written to develop the cognitive and emotional development of young children and aim to encourage active and responsible participation. Using plentiful illustrations, photocop.